Literasi Al-Qur’an pada Masa Golden Age: Analisis Efektivitas Metode Yanbu’a dalam Perspektif Behavioristik - Yaqin, Mukhamad Ainul; Sholihah, Nailatus (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2025)
Qur’anic literacy in early childhood is a crucial foundation for shaping Islamic character and religious identity during the formative years. This study aims to analyze the effectiveness of the Yanbu’a method in improving the ability to read and write the Qur’an among early learners at TPQ Darul Muttaqin, located in Plososari, Grati t, Pasuruan. The research employs a qualitative approach with a field study design. Data were collected through observation, interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman. The findings indicate that the Yanbu’a method has a positive impact on enhancing Qur’anic literacy in children aged 3 to 6. Its gradual, visual, and verbal approach fosters motivation, enthusiasm, and independent reading habits both within the institution and at home. The success of the method is also supported by the active role of teachers and a conducive learning environment. This study concludes that the Yanbu’a method is an effective instructional strategy for early childhood Qur’anic education in Islamic learning settings.